The Severians Ethnonym in the Writing Sources of the IX Century - Кириченко, Максим (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the analysis of the development of knowledge and ideas about ethnonyms in historiography and source study, which were similar to the name of the East Slavic tribal Union ‘Severians’, mentioned in the IX century sources (The Chronicle of Theophanes the Confessor and the Bavarian geographer). Various hypotheses regarding the interpretation of these ethnonyms and their ethnic attribution are considered. The author comes to the conclusion that, despite the fact that the studied ethnonyms are mainly associated with the Severians of Danube region, they also have a certain value for studying the historiography of the history of the Severians of the Left-bank of Dnieper, since they can reflect the stages of their migration from the Danube, according to some hypotheses and data of the Primary Chronicle.